Systematization of Sharh al-Hikam by Sheykh Nawawi al-Bantani in Kitab Misbah al-Dzulam - Khasani, Fahim; Amrullah, Latif (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
This study examines the systematization of Al-Hikam aphorisms as presented in the Misbah Al-Dzulam, and explores Sheykh Nawawi Al-Bantani’s methodology for interpreting Al-Hikam. Utilizing a descriptive analysis method, the research focuses on the aphorisms of Al-Hikam. The sequence of Al-Hikam is a subject of two contrasting views. The first perspective suggests that despite an apparent randomness, the original sequence of Al-Hikam serves a specific purpose, with a spiritual secret underlying its arrangement. The second view argues that there is no logical connection (irtibath mantiqi) between the initial and subsequent aphorisms. The systematic organization of these aphorisms facilitates to be studied. These divergent viewpoints have led to the creation of two models for studying Al-Hikam’s aphorisms: the tahlili model and the thematic model. The findings of this study reveal that the Misbah Al-Dzulam offers a systematic and categorized approach to Al-Hikam. This approach transforms the perceived randomness of Al-Hikam into a coherent and comprehensive structure, particularly when studied thematically. The tahlili method further enhances the study by integrating language analysis with Sufistic interpretive approaches. This study suggests to include this book in the advanced learning curricula for santri or Ma’had Aly.